Alumazene Reactivity with Quinolinols – Addition and Substitution Reactions on the Al3N3 Ring - Iva Kollhammerova; Michal Babiak; Marek Necas; Petr Taborsky; Josef Kucera; Jiri Pinkas (Acta Chimica Slovenica, 2018)
Molecular structures of two compounds obtained in reactions of alumazene [DippNAlMe]3 (1, Dipp = 2,6-i-Pr2C6H3) with substituted quinolinols have been elucidated by the single-crystal X-ray diffraction analysis. Quinolin-8-ol (Hq) provides a dinuclear complex [(DippNH)2Al2Me2(q)2] (2) with a central Al2O2 ring and five-coordinate Al atoms. The compound 2×THF crystallizes in the orthorhombic Pbca space group. The molecular structure of a mononuclear complex [(DippNH)Al(Meq)2] (3) obtained in the reaction of 1 with 2-methylquinolin-8-ol (HMeq) possesses a five-coordinate Al center. The structure was solved in a triclinic cell P-1. The dinuclear complex 2 can be considered as a model product of alcohol addition on the formal Al-N double bond, while the mononuclear complex 3 represents subsequent reaction of remaining Al-Me moiety with proton. Both complexes 2 and 3 are highly luminescent showing emission around 500 nm in solid state.